Structure, dynamics and movement patterns of the Australian pig industry. Issue 3 (9th February 2014) - East, IJ; Davis, J; Sergeant, ESG; Garner, MG
<x xml:space="preserve">Abstract</x> Objective To assess management practices and movement patterns that could influence the establishment and spread of exotic animal diseases (EAD) in pigs in Australia. Methods A literature review of published information and a telephone survey of 370 pig producers owning >10 pigs who were registered with the PigPass national vendor declaration scheme. Results The movement and marketing patterns of Australian pig producers interviewed were divided into two groups based predominantly on the size of the herd. Major pig producers maintain closed herds, use artificial insemination and market direct to abattoirs. Smaller producers continue to purchase from saleyards and market to other farms, abattoirs and through saleyards in an apparently opportunistic fashion. The role of saleyards in the Australian pig industry continues to decline, with 92% of all pigs marketed directly from farm to abattoir. Conclusions This survey described movement patterns that will assist in modelling the potential spread of EAD in the Australian pig industry. Continued movement towards vertical integration and closed herds in the Australian pig industry effectively divides the industry into a number of compartments that mitigate against the widespread dissemination of disease to farms adopting these practices.